Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Siswa - Nur Yulia Rahman; Haeril Haeril; Emmi Azis (Journal on Education, 2025)
This research uses this type of research quantitative with a one group pretest posttest research design. As for location research, namely at SMPN 2 Amali. The population of this research is class VIII SMPN 2 Amali while the sample for this study was class VIII A. Internal variables this research uses two variables, namely the independent variable is jigsaw type cooperative and the dependent variable is student learning outcomes. Instrument this research is a test sheet using pretest and posttest. Data analysis using the normality test and hypothesis testing using the SPSS 26 program. Referring to the average score on student learning outcomes, the pretest score is 42.05 and after being given treatment, the posttest score increased to reach 84.80. Because of this jigsaw type cooperative learning model, students can provide explanations and provide conclusions. This shows that the jigsaw type cooperative learning model provides a significant influence on student learning outcomes.